PENDAHULUAN DAN PELATIHAN SITUS GOOGLE SEBAGAI PORTOFOLIO DIGITAL SISWA SMK PGRI 16 JAKARTA - Bias Yulisa Geni, Desi Ramayanti, Giri Purnama (JURNAL BIMA, 2024)
In the current digital era, the ability to master information technology is an essential skill that must be possessed by every individual, including students. Introduction and training activities on the use of Google Sites as a digital portfolio are very important and provide great benefits, especially in helping students display their work and academic achievements in a professional and efficient way. This activity is designed to implement a Google Sites introduction and training program for students of SMK PGRI 16 Jakarta, aimed at improving their digital literacy skills and preparing them to face the challenges of the digital age. The approach taken in this activity is through practical training methods carried out interactively, accompanied by question and answer sessions to ensure a comprehensive understanding of the material provided. The results of this activity show a significant increase in students' abilities in creating and managing digital portfolios via Google Sites. This not only enhances their skills in information technology, but also provides them with an effective tool to present themselves and their work to a wider audience. From this activity, it can be seen that the integration of information technology in the world of education, especially through the use of Google Sites as a digital portfolio media, has great potential in increasing digital literacy and the readiness of students and students for future careers.